2017
DOI: 10.1155/2017/1093858
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nivolumab-Induced Severe Mononeuropathy Multiplex and Rhabdomyolysis

Abstract: We report an 81-year-old man with multiple liver metastases after tumorectomy for primary mediastinal malignant melanoma, who experienced limb weakness and sensory disturbance after nivolumab monotherapy. He was diagnosed with nivolumab-induced mononeuropathy multiplex and rhabdomyolysis based on serologic examination, muscle biopsy, magnetic resonance imaging of the limbs, and a nerve conduction study. A course of intravenous methylprednisolone (mPSL) was initiated at 1 g/day for 3 days. After that, oral pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…In addition, we discovered other single cases of very rare AEs in our cohort. Cases of rhabdomyolysis [21] or Guillain-Barré syndrome [22] following nivolumab treatment have already been reported, but these are known neurological complications of PD-1 antibodies and rare AEs of immunotherapy treatment [23]. Many results concerning safety data between the phase 3 study of Brahmer et al [10] and our study are similar; however, the frequency of severe AEs was different.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, we discovered other single cases of very rare AEs in our cohort. Cases of rhabdomyolysis [21] or Guillain-Barré syndrome [22] following nivolumab treatment have already been reported, but these are known neurological complications of PD-1 antibodies and rare AEs of immunotherapy treatment [23]. Many results concerning safety data between the phase 3 study of Brahmer et al [10] and our study are similar; however, the frequency of severe AEs was different.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, Sakai et al reported a case of a patient with metastatic melanoma treated with nivolumab who developed severe mononeuropathy multiplex and rhabdomyolysis. This patient did not have a pre-existing history of an underlying autoimmune condition and autoimmune serologies assessed after the onset of the patient’s symptoms were unremarkable [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above case is the first report describing severe immune-mediated myositis after a single dose of pembrolizumab. Katsuya et al encountered severe myositis with CK elevated to >27,000 U/L only 10 days after the first infusion; however, this was attributed to nivolumab ( Sakai et al, 2017 ). It is unclear if the same toxicity profiles apply to both nivolumab and pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%